2008
DOI: 10.1111/j.1365-3083.2007.02057.x
|View full text |Cite
|
Sign up to set email alerts
|

Human B Cells and Macrophages Cooperate in T‐cell‐independent Type 2 Response

Abstract: We have analysed separately the role of B‐cell receptor (BCR) stimulation and the soluble second signal in the T‐cell‐independent type 2 (TI‐2) B‐cell response. We were able to show that human B cells and macrophages (Mφ) could function together in TI‐type microbial response. Interestingly, BCR cross‐linking of peripheral blood (PB) B cells enhanced IgG production induced by Mφ‐derived growth factors whereas interleukin (IL)‐12 + IL‐18 had milder effect on IgG production. We demonstrated that B‐cell‐derived so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…RTX depletes B cells through antibody-dependent cellular cytotoxicity, complement-dependent cytotoxicity, and apoptosis [ 28 , 29 ], which determine the therapeutic use in malignant B-cell lymphoma [ 30 ], and the reduced auto-antibodies in various autoimmune disorders [ 31 , 32 ]. Moreover, B cells had an additional role in producing permeability factors with T cells, which provided a rationale for RTX therapy [ 33 ]. Interestingly, Fornoni et al [ 34 ] found that RTX prevents the disruption of podocyte apoptosis and actin cytoskeleton through the phosphodiesterase acid-like 3b.…”
Section: Discussionmentioning
confidence: 99%
“…RTX depletes B cells through antibody-dependent cellular cytotoxicity, complement-dependent cytotoxicity, and apoptosis [ 28 , 29 ], which determine the therapeutic use in malignant B-cell lymphoma [ 30 ], and the reduced auto-antibodies in various autoimmune disorders [ 31 , 32 ]. Moreover, B cells had an additional role in producing permeability factors with T cells, which provided a rationale for RTX therapy [ 33 ]. Interestingly, Fornoni et al [ 34 ] found that RTX prevents the disruption of podocyte apoptosis and actin cytoskeleton through the phosphodiesterase acid-like 3b.…”
Section: Discussionmentioning
confidence: 99%